2018
DOI: 10.4038/sljch.v47i1.8428
|View full text |Cite
|
Sign up to set email alerts
|

Blood lactate as a predictor of mortality in critically ill children

Abstract: Objective: To study blood lactate levels at admission in predicting mortality in critically ill children requiring haemodynamic / respiratory support.Method: A prospective observational study was done in 200 critically ill admissions to the paediatric intensive care unit (PICU), requiring haemodynamic / respiratory support. The demographic data, clinical status, organ involvement and therapeutic interventions were recorded in a predesigned proforma until hospital discharge or death. Lactate levels were estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…In a study by Bai Z et al (13), the median blood lactate level measured in critically ill patients was 3.2 mmol/L (2.2-4.8 mmol/L). Similarly, in a study by Chanderashekher et al (9), the mean lactate level among survivors was 2.28, and in a study by Gupta A et al (8), it was 2.77±1.77 mmol/L, which was comparable to the present study, where blood lactate was 2.95 mmol/L (1.83-4.48 mmol/L). In a retrospective cohort study by Morris KP et al (14), admission lactate in PICU non-survivors (6.6 mmol/L (SD=5.6)) was higher than in survivors (3.0 mmol/L (SD=2.5)), with a positive association with mortality.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In a study by Bai Z et al (13), the median blood lactate level measured in critically ill patients was 3.2 mmol/L (2.2-4.8 mmol/L). Similarly, in a study by Chanderashekher et al (9), the mean lactate level among survivors was 2.28, and in a study by Gupta A et al (8), it was 2.77±1.77 mmol/L, which was comparable to the present study, where blood lactate was 2.95 mmol/L (1.83-4.48 mmol/L). In a retrospective cohort study by Morris KP et al (14), admission lactate in PICU non-survivors (6.6 mmol/L (SD=5.6)) was higher than in survivors (3.0 mmol/L (SD=2.5)), with a positive association with mortality.…”
Section: Discussionsupporting
confidence: 88%
“…The PRISM III score was significantly higher in patients who died (P=0.001), i.e., the PRISM III score was significantly associated with survival outcome in patients admitted to the PICU. The patient survival rate in the present study was 90.7%, but a few other studies showed the survival rate as 67% by Gupta A et al (8), 50% by Jat et al (12), and 24% by Chanderashekher et al (9). Therefore it is recommended that mortality risk is assessed using PRISM III at admission, as it is simple to use.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations